Synthesis and chiral resolution of C3-Symmetric tribenzotriquinacenes - Beaudoin, Daniel; Rominger, Frank; Mastalerz, Michael (European journal of organic chemistry, 2016)
The synthesis and chiral resolution of a C3-symmetric triaminotribenzotriquinacene is reported. Both enantiomers were obtained in good yields and excellent enantiomeric purity by selective precipitation of their monodibenzoyltartrate salts. Conversion of the enantiopure (M)-triaminotribenzotriquinacene into a C3-symmetric triiodide highlights the usefulness of this compound as a starting point for the preparation of other enantiopure C3-symmetric tribenzotriquinacene derivatives, which may find application as building blocks for the preparation of chiral molecules in the nanosize regime.